Effect of UV radiation on habitat selection by Girella laevifrons and Graus nigra (Kyphosidae). Issue 2 (4th January 2015) - Pulgar, J.; Lagos, P.; Maturana, D.; Valdés, M.; Aldana, M.; Pulgar, V. M.
<x xml:space="preserve">Abstract</x> The effect of UV radiation on habitat use of two species of intertidal fishes that inhabit the same pools but exhibit different activity levels and diets was measured: the highly active omnivorous Girella laevifrons and the cryptic carnivorous Graus nigra. Individuals of each species were acclimated to a tank divided in three sections with different illumination; no light (NL), ultraviolet light (UV) and white light (WL), and the time spent and number of visits to each section were recorded. Although both species preferred the NL section, G. laevifrons spent more time in UV and less time in WL compared with G. nigra; G. laevifrons also displayed higher number of visits to UV, suggesting a different tendency in space use in response to UV exposure in intertidal fishes.